Comment-Advanced Early Jurassic Termite (Insecta:Isoptera) Nests: Evidence from the Clarens Formation in the Tuli Basin, Southern Africa (Bordy et al., 2004) - Genise, Jorge Fernando (2005)
The contribution by Bordy et al. (2004) lacks the pertinent macro and micromorphological analyses and comparisons with modern nests that would allow their attribution to termites. It also lacks any analysis about the age of the structures in comparison with the bearing rocks. In addition, the described features are not indicative of termitic origin, as summarized below: (a) Eolian dunes as those described from the Clarens Formation, are inhabited only by few termites that construct no mounds, but completely subterranean nests. In addition, this environment is poorly vegetated or lacks any vegetation at all, which would not support large colonies of termites; (b) The features and size of the interconnecting bioturbated cylinders are not compatible with any known termite gallery; (c) The orientation of the structures is not diagnostic of termite nests, even less, when pillars, ?buttresses? and ?bioturbated cylinders? show the same orientation; (d) The purported buttresses are almost unknown for termite nests and show a close resemblance to structural joints; (e) Type 1 burrows lack a detailed description and interpretation. For this reason, it is impossible to attribute them to social or solitary organisms, even less to termites when branching is rare; (f) The attribution of type 2 burrows to ants is unsupported. Besides, this aspect is not critical to the identification of termite nests; (g) Type 3 burrows display characteristics that occur in a wide array of sedimentary deposits and are not diagnostic of termite nests; (h) The wall of the purported termite nests is an order of magnitude thinner than the same structure in modern termite nests; (i) The absence of clay in the structures is contradictory with the inferred fungus-growing termites, because the clay content of soil is critical for the construction of these subaerial nests; (j) The presence of advanced fungus-growing termites as purported producers of the Tuli structures is unlikely by the early Jurassic, considering that the oldest termites come from the Cretaceous, and  there is no record of grasslands and gilled fungus until the Tertiary.In consequence, it is considered that the interpretation of the Tuli structures as termite nests is unsubstantiated and should be revised.